2.73. Korzystając z definicji, oblicz pochodna funkcji fw punkcie x 0 : a) f(x) = 2x ^ 3 x 0 =5 c) f(x)= x+3 x-5 ,x 0 =1 e) f(x) = sqrt(3x + 6) , x 0 =1 b) f(x) = – x ^ 3 + x ^ 2 – x , x 0 =-2 f(x) = (- 3x)/(x + 1) f(x) = sqrt(1 – 5x) , x 0 =-3 d) x 0 =-2

2.73. Korzystając z definicji, oblicz pochodna funkcji fw punkcie x 0 : a) f(x) = 2x ^ 3 x 0 =5 c) f(x)= x+3 x-5 ,x 0 =1 e) f(x) = sqrt(3x + 6) , x 0 =1 b) f(x) = – x ^ 3 + x ^ 2 – x , x 0 =-2 f(x) = (- 3x)/(x + 1) f(x) = sqrt(1 – 5x) , x 0 =-3 d) x 0 =-2

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz